Genotype-by-culture-system interaction in catla and silver carp: Monoculture and biculture: Data - Hamilton, Matthew (2023)
Weight data for fish analysed in Hamilton M.G., Mekkawy W., Alam M.B., Barman B.K., Karim M. & Benzie J.A.H. (2023) Genotype-by-culture-system interaction in catla and silver carp: Monoculture and biculture